2016
DOI: 10.1002/jcu.22357
|View full text |Cite
|
Sign up to set email alerts
|

Layer-specific analysis of left ventricular myocardial contractility in patients with coronary slow-flow phenomenon

Abstract: The LS of all three myocardial layers was lower in patients with CSFP than in controls. In patients with CSFP, LS of all three myocardial layers and transmural LS gradient correlated negatively with the number of affected coronary arteries and the mean thrombolysis in myocardial infarction frame count. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44:429-436, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
0
13
2
Order By: Relevance
“…[22][23][24] Previous studies have reported layer-specific strain differences in patients with a non-ST-segment elevation acute coronary syndrome and chronic ischemic cardiomyopathy. 25,26) Wang, et al 27) have analyzed the LV three-layer strain in patients with CSF; however, they did not show the layerspecific difference in the strain values reflecting the inhomogeneous pathologic change in the endocardium and the midwall layer, which was well evaluated in our study. 2D-STI has been performed extensively to evaluate LV function in various cardiac conditions.…”
Section: Discussioncontrasting
confidence: 53%
“…[22][23][24] Previous studies have reported layer-specific strain differences in patients with a non-ST-segment elevation acute coronary syndrome and chronic ischemic cardiomyopathy. 25,26) Wang, et al 27) have analyzed the LV three-layer strain in patients with CSF; however, they did not show the layerspecific difference in the strain values reflecting the inhomogeneous pathologic change in the endocardium and the midwall layer, which was well evaluated in our study. 2D-STI has been performed extensively to evaluate LV function in various cardiac conditions.…”
Section: Discussioncontrasting
confidence: 53%
“…The greater the value of mTFC is, the more impaired the longitudinal systolic function of both ventricles (Figure ). This finding can be explained by the slower coronary flow (indicated by a greater mTFC), which represents more serious coronary artery involvement in patients with CSFP . In addition, slower coronary flow may affect the timely compensation of collateral circulation, which in turn may lead to myocardial ischemia and subclinical systolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…This finding can be explained by the slower coronary flow (indicated by a greater mTFC), which represents more serious coronary artery involvement in patients with CSFP. 31 In addition, slower coronary flow may affect the timely compensation of collateral circulation, which in turn may lead to myocardial ischemia and subclinical systolic dysfunction. This finding supports the long-term follow-up of CSFP patients, especially those with greater mTFC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our previous study revealed that left ventricular (LV) systolic and diastolic functions in patients with CSFP are impaired at rest [8,9]. Therefore, patients with CSFP should receive close attention.…”
Section: Introductionmentioning
confidence: 99%